The role of exogenous glycinebetaine on some antioxidant activity of non-T and T tobacco (Nicotiana tabacum L.) under in vitro salt stress - Marzeih VAHID DASTJERDI; Ali Akbar EHSANPOUR; Amir Hossein FORGHANI (Acta Agriculturae Slovenica)
Glycine betaine is an osmoprotectant compound which enhances cell tolerance in plant species in response to environmental stresses. This study aimed to investigate the effect of exogenous application of glycine betaine on some antioxidant activities of tobacco plants overexpressing P5CS gene. Sterile tobacco seedlings with four to six leaves were transferred to MS medium containing 0, 100, and 200 mM NaCl, after which glycine betaine (20 and 40 mg l-1) were foliar sprayed on the surface of the plants. After four weeks, glycine betaine treatment enhanced the antioxidant capacity of the plant through activation of catalase (CAT), superoxide dismutase (SOD), and ascorbate peroxidase (APX). In contrast, H2O2 content and MDA level were reduced by glycine betaine under similar conditions. Therefore, application of exogenous glycine betaine under salt stress improved stress tolerance in T and non-T plants. Meanwhile, our results indicated the positive effect of glycine betaine in T plants was greater than in non-T plants. On the other hand, this result suggested that the synergistic effects of glycine betaine and proline in plants enhanced the antioxidant defense system in T plants overexpressing P5CS gene.